2021
DOI: 10.1016/j.ultsonch.2021.105832
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound cavitation induced nucleation in metal solidification: An analytical model and validation by real-time experiments

Abstract: Highlights An analytical model is developed to predict the cavitation induced undercooling, grain nucleation and the solidified grain size. Cavitation bubble implosion in metallic melts were imaged in-situ by ultrafast synchrotron X-ray imaging. The model takes into account of ultrasound input intensity, cavitation bubble size and the effect of melt temperature. The solidified grain size of different alloys were calculated using this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Simultaneously, the Cu joints using Ni-Sn composite solder are contributed to grain refinement through ultrasonic-assisted soldering [46] , [47] , [48] . Many studies have shown that applying ultrasonic treatment can optimize the microstructure, refine the grain and improve the mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the Cu joints using Ni-Sn composite solder are contributed to grain refinement through ultrasonic-assisted soldering [46] , [47] , [48] . Many studies have shown that applying ultrasonic treatment can optimize the microstructure, refine the grain and improve the mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Few alloys solidify with a large fraction of primary intermetallic phases (mainly Al alloys used in non-structural components compared to Mg alloys) in which the dominant mechanism for refinement is fragmentation by cavitation and fluid flow, although some oxide particles are found as nucleating substrates after UST [43] , [73] . The refinement induced by cavitation and acoustic streaming (for a given volume of melt) is dependent on the intensity of the applied power of UST [74] . However, for the separation mechanisms listed in Fig.…”
Section: Ultrasonic Processing Conditions Alloy Systems and Solidific...mentioning
confidence: 99%
“…Therefore, the development of primary α(Al) dendrites constructing a network during solidification is an essential inhibitory factor to the casting fluidity. It has been found that ultrasonic vibration could significantly influence the solidification of aluminum alloy [15,16] . Especially, the acoustic cavitation can break the dendrites during solidification [17,18] .…”
Section: Influence Of Displacement Gradient On Melt Fluiditymentioning
confidence: 99%